Penguatan Keterampilan Kolaborasi Dalam Pembelajaran Kelas 1 Sekolah Dasar: Analisis Kritis - Iin Inayati; Roshayanti, Fenny; Sulianto, Joko (Jurnal Ragam Pengabdian, 2026)
Learning in elementary schools requires the development of 21st-century skills, one of which is collaboration, which serves as a foundation for students' social interaction (Maharani et al., 2024). This study aims to critically analyze the implementation of collaborative learning among first-grade elementary school students as well as the factors that influence it (Yubi et al., 2024). The method used is a literature review by analyzing various scientific journals relevant to the topic of student collaboration (’Ula et al., 2024). The results of the study indicate that collaborative learning can improve students' social skills, learning motivation, and conceptual understanding (Astria et al., 2025). However, its implementation still faces challenges such as students' limited communication skills and teachers' readiness in managing collaborative learning (Syarif, 2023). Social constructivism theory from Vygotsky and cognitive development theory from Piaget reinforce the importance of social interaction in the student learning process (Vygotsky, 1978). Therefore, well-planned instructional strategies that align with the characteristics of lower-grade students are needed to ensure that collaboration can be carried out optimally (Wahyuni & Muhibbin, 2024).